(untitled) (Eurasian Journal of Ecology, 2025)
This research investigates the histomorphological alterations in rat testes under varying doses of cadmium chloride exposure, as well as explores the effectiveness of Taraxacum officinale extract in correcting these observed tissue disruptions. The primary objective is to assess the degree of damage to the spermatogenic epithelium and interstitial tissue caused by the toxic metal, while also determining the potential gonadoprotective function of the herbal extract. The scientific and practical significance of this research is grounded in the pressing issue of metal-induced toxicity leading to impaired reproductive capacity, underlining the need for preventive measures that safeguard fertility. Three different doses of cadmium chloride were administered, followed by the introduction of the dandelion extract to a subset of experimental animals. Methodologically, hematoxylin and eosin staining of testicular sections provided a means to evaluate the state of the seminiferous tubules, measure edema in the interstitial space, and detect necrotic changes. Findings indicated that lower doses of cadmium prompted only minor toxic effects, whereas higher concentrations resulted in notable epithelial necrosis and disruption of tubule morphology. Meanwhile, Taraxacum officinale extract significantly reduced these adverse effects. The contribution of this work lies in verifying the extract’s antioxidant and anti-inflammatory properties, paving the way for expanded use of plant-based interventions in preventing and treating cadmium intoxication. The practical relevance is reflected in the prospect of incorporating Taraxacum officinale as a viable component of therapeutic strategies aimed at preserving male reproductive function. Keywords: testes, cadmium chloride, Taraxacum officinale, histomorphology, reproductive health